Relationship Between Pneumocystis carinii Burden and the Degree of Host Immunosuppression in an Airborne Transmission Experimental Model. (24th November 2015) - Khalife, Sara; Chabé, Magali; Gantois, Nausicaa; Audebert, Christophe; Pottier, Muriel; Hlais, Sani; Pinçon, Claire; Chassat, Thierry; Pierrot, Christine; Khalife, Jamal; Aliouat‐Denis, Cécile‐Marie; Aliouat, El Moukhtar
Abstract: To quantitatively assess the risk of contamination by Pneumocystis depending on the degree of immunosuppression (ID) of the exposed rat hosts, we developed an animal model, where rats went through different doses of dexamethasone. Then, natural and aerial transmission of Pneumocystis carinii occurred during cohousing of the rats undergoing gradual ID levels (receivers) with nude rats developing pneumocystosis (seeders). Following contact between receiver and seeder rats, the P. carinii burden of receiver rats was determined by toluidine blue ortho staining and by qPCR targeting the dhfr monocopy gene of this fungus. In this rat model, the level of circulating CD4 + and CD8 + T lymphocytes remained significantly stable and different for each dose of dexamethasone tested, thus reaching the goal of a new stable and gradual ID rat model. In addition, an inverse relationship between the P. carinii burden and the level of circulating CD4 + or CD8 + T lymphocytes was evidenced. This rat model may be used to study other opportunistic pathogens or even co‐infections in a context of gradual ID.